Contagion [videorecording (DVD)] - Soderbergh, Steven, 1963-; Winslet, Kate; Fishburne, Laurence, III, 1961-; Damon, Matt; Paltrow, Gwyneth, 1972-; Law, Jude, 1972- (Warner Home Video, 2011)
A thriller centered on the threat posed by a deadly disease and an international team of doctors contracted by the CDC to deal with the outbreak.